Peritoneal Cytokines as Early Biomarkers of Colorectal Anastomotic Leakage Following Surgery for Colorectal Cancer: A Meta-Analysis - Qi, Xin-Yu; Liu, Mao-Xing; Xu, Kai; Gao, Pin; Tan, Fei; Yao, Zhen-Dan; Zhang, Nan; Yang, Hong; Zhang, Cheng-Hai; Xing, Jia-Di; Cui, Ming; Su, Xiang-Qian (Frontiers in Oncology, 2022)
Background: Postoperative colorectal anastomotic leakage (CAL) is a devastating complication following colorectal resection. However, the diagnosis of anastomotic leakage (AL) is often delayed because the current methods of identification are unable to achieve 100% clinical sensitivity and specificity. This meta-analysis aimed to evaluate the predictive value of peritoneal fluid cytokines in the detection of CAL following colorectal surgery. Methods: A comprehensive search was conducted on PubMed, Embase, Cochrane Library, and Web of Science before June 2021 to retrieve studies regarding peritoneal fluid cytokines as early markers of CAL. Pooled analyses of interleukin (IL)-1β, IL-6, IL-10, and tumor necrosis factor (TNF) were performed. The means (MD) and standard deviations (SD) of the peritoneal fluid cytokines were extracted from the included studies. Review Manager Software 5.3 was used for data analysis. Results: We included eight studies with 580 patients, among which 85 (14.7%) and 522 (44.5%) were evaluated as the CAL and non-CAL groups, respectively. Compared to the non-CAL group, the CAL group had significantly higher peritoneal IL-6 levels on postoperative day (POD) 1–3 (P = 0.0006, 0.0002, and 0.002, respectively) and slightly higher TNF levels on POD 4 (P = 0.0002). Peritoneal levels of IL-1β and IL-10 were not significantly different between the two groups in this study. Conclusion: Peritoneal IL-6 levels can be a diagnostic marker for CAL following colorectal surgery, whereas the value of TNF needs further exploration in the future. Systematic Review Registration: PROSPERO (CRD42021274973)